Research on Flight Training Optimization with Instrument Failure Based on Eye Movement Data - Jiwen Tai; Yu Qian; Zhili Song; Xiuyi Li; Ziang Qu; Chengzhi Yang (Journal of Eye Movement Research)
To improve the quality of flight training in instrument failure scenarios, eye movement data were collected from flight instructors during climbing, descending, and turning flights when the primary attitude direction indicator failed. The performance data of the excellent instructors was selected to produce eye movement tutorials. These tutorials were used to conduct eye movement training for the experimental group of flight trainees. In contrast, the control group received traditional training. The performance and eye movement data of the two groups of flight trainees were then compared and analyzed. The results showed that flight trainees who received eye movement training performed better when facing instrument failure. Specifically, the deviations in the rate of descent, heading during the descent, airspeed during the turn, and slope during the turn were significantly different from those of the control group. Compared to the control group, the experimental group had a significantly lower fixation frequency on the failed instrument during the turn. Additionally, the average glance duration on the failed instrument during the climb and turn was significantly reduced. The study demonstrated the effectiveness of eye movement training in improving the quality of flight training in instrument failure scenarios.